NON-PROFIT ORGANIZATIONS AND TOURISM: CAN TOURISM DRIVE NON-PROFIT SECTOR DEVELOPMENT? - Lorena Dadic Fruk; Jelena Durkin Badurina; Helga Maškarin Ribaric (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
Non-profit sector development is the basis of any modern society. Various approaches, which take into consideration a broad spectrum of factors, are used in measuring the level of non-profit sector development. Previous studies do not identify tourism as a potential factor. It can, however, be assumed that local authorities in better-developed tourism regions are able to allocate more funds to non-profit activities, thus affecting the size of the non-profit sector. It would also be necessary to investigate whether nonprofit organizations (NPOs) recognise the potential that tourism has to provide them with opportunities to generate their own income. To determine the relationship between tourism and the non-profit sector, cluster analysis was conducted for 20 Croatian counties. The results of the study show that the level of tourism development determines the development of the non-profit sector. Namely, results confirm that there are more NPOs in regions with more-developed tourism and there are also more NPOs registered in fields of activity that can have a direct or indirect effect on tourism. On the other hand, the study’s findings indicate that regions with developed tourism tend to allocate more funds to NPO activity, which in turn boosts the level of non-profit sector development in those regions. Although this research focused on only one country and deal with certain challenges in administrative data on registered non-profit organisations, it is promising start for development of new lines of research oriented on connecting non-profit and tourism sector and examining their inter-dependence.